STUDY ON THE EXPERIENCES AND EMOTIONS ASSOCIATED WITH HAPPINESS AMONG HIGH SCHOOL STUDENTS (The Journal of Psychology and Sociology, 2024)
The study of happiness focuses on how people perceive their well-being, the ways they seek happiness, and the factors that affect their feelings of happiness, including self-esteem, depression, satisfaction, and living quality. Researchers also aim to explore the relationship between happiness, self-esteem, depression, satisfaction, and quality of life, to assess people's sense of achievement. Happiness is strongly linked to an individual's sense of achievement and overall life satisfaction. In this article, we will discuss the findings of a study that examines the feelings of happiness and the factors that influence them among 562 high school students.The research discovered that students from both China and Mongolia shared a similar understanding of happiness. There are no differences in how Chinese and Mongolian students perceive happiness. It has been discovered that happiness plays a crucial role in making people better citizens. Studies have shown that it is a strong predictor of civic engagement when growing up and becoming an adult. Moreover, positive emotions that lead to career success help improve work results. As a result, it is advised to organize various activities that aim to develop students' sense of happiness in general education schools.Key words: happiness, high school students, feelings of happiness, happiness level.